2013
DOI: 10.1007/s11414-013-9338-y
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Utilization and Symptom Variation Among Veterans Using Behavioral Telehealth Center Services

Abstract: Substance use and mental health problems are often underdiagnosed and undertreated in primary care. Veterans affairs facilities are using the Behavioral Telehealth Center (BTC) to provide evidence-based assessments for primary care patients via telephone. Whether participation in BTC services is associated with (1) increases in healthcare utilization and (2) decreases in symptoms based on behavioral health screening instruments, post-BTC services compared with pre-BTC services were investigated. Retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Previous studies have also found that maintaining a healthy lifestyle can promote individuals’ health and reduce the utilization of medical resources (Possemato, Bishop, Willis, Lantinga, ; Wiley‐Exley et al, ). Individuals who are more motivated to maintain personal health are likely to lead healthy lifestyles (i.e., to have exercise habits) and understand the importance of undergoing health examinations, increasing the likelihood of their use of preventive health services (Lee, Chang, & Du, ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have also found that maintaining a healthy lifestyle can promote individuals’ health and reduce the utilization of medical resources (Possemato, Bishop, Willis, Lantinga, ; Wiley‐Exley et al, ). Individuals who are more motivated to maintain personal health are likely to lead healthy lifestyles (i.e., to have exercise habits) and understand the importance of undergoing health examinations, increasing the likelihood of their use of preventive health services (Lee, Chang, & Du, ).…”
Section: Discussionmentioning
confidence: 97%
“…Third, the remaining patients who did not meet any of these previous criteria were then grouped into "Antidepressants for Other Psychiatric Condition" (PsychRx) if they received one or more antidepressant medication orders (RxNorm Healthcare utilization. Depression is associated with increased healthcare utilization (Bhattarai et al, 2013;Felleman et al, 2013;Possemato et al, 2013). As a measure of healthcare utilization, we calculated the average number of visits annually across different health care settings and compared these across the groups.…”
Section: Methodsmentioning
confidence: 99%
“…As COVID-19 restrictions continue to impact health service delivery, health care providers and insurers are positioned to assess whether clients consider virtual treatment delivery to be acceptable, and to extract clients' suggestions for improving the acceptability. Research has shown that virtual adaptations can be effective (Possemato, Bishop, Willis, & Lantinga, 2013), provided that clients feel their confidentiality is protected (Bischoff, Hollist, Smith, & Flack, 2004) and continue to feel engaged by a "real" person behind the virtual space (Mohr, Cuijpers, & Lehman, 2011). However, such studies took place prior to COVID-19.…”
Section: Future Researchmentioning
confidence: 99%